Windrow composting of municipal biosolids in a cold climate. Issue 5 (1st September 2005) - Eftoda, Grant; McCartney, Daryl
Abstract : This work investigated the technical feasibility of composting digested municipal biosolids using outdoor windrows in an extremely cold climate. Common belief suggested this was not possible because of low ambient temperatures and low biodegradable volatile solids content of the biosolids. Four trials were conducted: ( i ) batch started in late fall; ( ii ) batch started in winter; ( iii ) batch mixed and stored over winter, then started in spring; and ( iv ) batch mixed with leaves to improve heat generation. All recipes used 2.5 parts wood chips to 1 part biosolids (by volume). All four trials easily met the thermophilic temperatures required by the pathogen reduction criteria. Trial 2 (batch started in winter), however, did not achieve the thermophilic period until the following summer. The results suggest provisions be made for storage of material over winter. This means a 32% increase in area and a doubling of the system-turning capacity are needed. Practical observations included significant heat loss during turning and mixing, snowfall impact on oxygen supply and pile moisture content, wind direction impact on pile temperature profiles, and the impact of large frozen zones that may affect pathogen inactivation efficacy.